Tailoring strain rate sensitivity and creep behavior of CoCrNi multi-principal-element alloys by aging - Zhanxuan Zhang; Weize Kong; Qiang Zhang; Kaiyuan Yu (Journal of Materials Research and Technology)
While simulations predict that local chemical order in multi-principal-element alloys (MPEAs) renders anomalous dislocation behaviors and thereby varied strain rate sensitivity (SRS) and creep behaviors, the experimental demonstration of such an effect is still under exploration due to the challenges in the manipulation of local chemical order. Here we investigate SRS and creep behavior of CoCrNi MPEAs subjected to long-term aging at various temperatures using nanoindentation. Our results reveal that the SRS and creep resistance of the alloys enhance significantly with increasing aging temperatures, with the SRS notably surpassing that of elemental and solid solution counterparts. In particular, unusual magnitude of creep stress exponent is observed at room temperature and the possible mechanisms are discussed. We suggest that long-term aging could be a straightforward method to tailor the microstructural ordering and mechanical properties of MPEAs, aiming at bridging the gap between simulations and experiments.